Art, Craft and Art and Craft Syllabuses: Effective for Examination from May 1992 - Caribbean Examinations Council (Caribbean Examinations Council, 1992)
These syllabuses in Art, Craft, Art and Craft provide students not only with a basis for further study but also enhance leisure-time pursuits and/or vocational skills. The major revisions to this syllabus for 1992 are: (i) the discontinuation of the subject offerings at Basic Proficiency; (ii) the introduction of an alternative scheme of certification at General Proficiency; (iii) the introduction of a fifth option – Decorative Craft – to the Craft syllabus.
Keywords: CXC syllabus